2011
DOI: 10.1063/1.3533816
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced evolution of surface-potential undulation observed on vacuum-deposited thin films of tris(8-hydroxyquinolinato) aluminum

Abstract: We investigated surface-potential (SP) undulation on thin films of tris(8-hydroxyquinolinato) aluminum (Alq3) using Kelvin probe force microscopy with intermittent photoexposure. SP undulation with a cloudlike morphology of 200–300 nm in lateral size was observed for Alq3 films of 10–200 nm in thickness. A short photoexposure increased the SP undulation approximately twice as that of the unexposed values, while the SP average decreased monotonically. We analyzed the origin of the SP undulation and the mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 24 publications
(22 reference statements)
0
10
2
Order By: Relevance
“…In the case of Alq 3 films, GSP decayed irreversibly upon light absorption because photocarriers in the film accumulated at the film surface to cancel GSP. 19,24,25 Our result suggests an inefficient generation of photocarriers in the BCP layer compared to Alq 3 . On the other hand, the SP of junction C before BCP deposition was 0.3 V [ Fig.…”
Section: A Kelvin Probe Measurementsmentioning
confidence: 67%
See 1 more Smart Citation
“…In the case of Alq 3 films, GSP decayed irreversibly upon light absorption because photocarriers in the film accumulated at the film surface to cancel GSP. 19,24,25 Our result suggests an inefficient generation of photocarriers in the BCP layer compared to Alq 3 . On the other hand, the SP of junction C before BCP deposition was 0.3 V [ Fig.…”
Section: A Kelvin Probe Measurementsmentioning
confidence: 67%
“…The responsiveness to the light of SP in junction C was evaluated by irradiation from a halogen lamp though a glass viewport without any filter. Because GSP is likely to decay upon light absorption of the film, 19,24,25 all the above procedures except the photoresponse measurements were performed in the dark.…”
Section: Methodsmentioning
confidence: 99%
“…Complementary studies using optical second harmonic generation revealed that GSP originates from SOP, i.e., the spontaneous order of the PDMs of Alq 3 [10,31]. At the initial stage, researchers have focused on the photoinduced decay mechanism of GSP mainly motivated by the interests of fundamental material science rather than device physics [10,[32][33][34][35]. GSP/SOP is not a unique property of Alq 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Because of the photoinduced decay nature [10,[31][32][33], GSP has initially not been considered as an important parameter in terms of device properties. People have believed that no influences remain in actual devices of OLEDs after vanishing GSP due to the absorption of the ambient light and emission from the device itself.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the photoinduced decay nature, 3,5,10,11 GSP has not been considered as an important parameter in terms of device properties; however, the orientation polarization is maintained in the actual devices and induces a negative polarization charge at the heterojunctions in these devices. 2,12 The negative interface charge governs the hole injection and accumulation properties.…”
mentioning
confidence: 99%